1991
DOI: 10.1063/1.461763
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of polarizabilities, potentials, and geometries of alkali–halide dimers

Abstract: An analysis of electronic polarizabilities, interionic potentials, and equilibrium geometries for 20 alkali–halide dimers such as Na2Cl2 is presented. The electronic polarizabilities of ions in dimers have been calculated by taking account of the electrostatic potential due to neighboring ions within the Seitz–Ruffa energy level analysis. The polarizabilities thus obtained for dimers are then used to evaluate the magnitudes of polarization energies and van der Waals dipole–dipole energies. For describing the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…The "effective" polarizability for Cl ions derived by optimizing the calculations for the experimental results occurred to be ≈2 Å 3 , as has been shown in the Figure 1c. This is close to the calculated value for a dimer of 2.24 Å 3 by Chauhan et al 17 The four vertical lines at the bottom of the experimental spectra in Figure 2a correspond to the binding energies of the four sites calculated with this "effective" polarizability value. Despite the relatively simple model, good agreement with the experiment is observed.…”
Section: The Journal Of Physical Chemistry Asupporting
confidence: 89%
See 1 more Smart Citation
“…The "effective" polarizability for Cl ions derived by optimizing the calculations for the experimental results occurred to be ≈2 Å 3 , as has been shown in the Figure 1c. This is close to the calculated value for a dimer of 2.24 Å 3 by Chauhan et al 17 The four vertical lines at the bottom of the experimental spectra in Figure 2a correspond to the binding energies of the four sites calculated with this "effective" polarizability value. Despite the relatively simple model, good agreement with the experiment is observed.…”
Section: The Journal Of Physical Chemistry Asupporting
confidence: 89%
“…In the earlier works it has been suggested that the chlorine polarizability reported to be from 3.66 Å 3 28 to 3.94 Å 3 , 29 in a free ion should be "quenched" already in a molecule by about 30−40%. 17,30 For an alkali metal halide dimer the polarizability of halide anions, determining the larger part of the polarization interaction, has been estimated to decrease further by about ≈10%. 17 Theory suggests that the polarizability decreases even further when the number of neighbors grows.…”
Section: Ionic Model and The Role Of Its Main Parameters For Alkali M...mentioning
confidence: 99%
“… a Distances in pm, angles in degrees. b Langhoff et al c Dickey et al d Lintuluoto e Iron et al f Modisette et al g Chauhan et al h Welch et al i Brumer et al …”
Section: Results and Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14] Within the class of lithium bromide clusters, very few data on the stoichiometric Li n Br n and Li n Br clusters can be found in literature. [15][16][17][18][19][20][21] The theoretical study by Hebant and Picard has shown that Li 2 Br features C 2v symmetry, where the Li-Br-Li bond angle is 72.31 , and the Li-Br bond length is 2.38 Å. These authors found that the solubility of the metal in halides can be explained by formation of compounds such as Li 2 X (X = F, Cl, Br and I).…”
Section: Introductionmentioning
confidence: 99%